2021
DOI: 10.1101/2021.06.26.450022
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Snail maintains the stem/progenitor state of skin epithelial cells and carcinomas through the autocrine effect of the matricellular protein Mindin

Abstract: Intratumoral heterogeneity poses a major challenge in designing effective anti-cancer strategies. Accumulating evidence suggests that this heterogeneity arises from cancer stem cells (CSCs) that also drives tumor aggressiveness and drug resistance. The stemness of CSCs are preserved by an ill-defined combination of intrinsic and external factors and is particularly intriguing since they exist within a sea of similar cells at various degrees of differentiation. In models of cutaneous squamous cell carcinoma (cS… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 77 publications
(102 reference statements)
0
4
0
Order By: Relevance
“…We recently observed that the matricellular protein Mindin (Spondin-2) is secreted from Snail Tg keratinocytes 18,21 and is required for the expression of inflammatory cytokines in dermal fibroblasts and fibrosis in the transgenic mouse 18 . To test if Mindin is also required for the relocalisation of Sca1+ fibroblast towards the epidermal-dermal junction in the Snail Tg skin we stained Sca1+ fibroblasts (Figure 2A) and quantified (Figure 2B, S2A) their localization in P9 WT, Snail Tg, and Snail Tg/Min KO (Mindin knockout) skin.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We recently observed that the matricellular protein Mindin (Spondin-2) is secreted from Snail Tg keratinocytes 18,21 and is required for the expression of inflammatory cytokines in dermal fibroblasts and fibrosis in the transgenic mouse 18 . To test if Mindin is also required for the relocalisation of Sca1+ fibroblast towards the epidermal-dermal junction in the Snail Tg skin we stained Sca1+ fibroblasts (Figure 2A) and quantified (Figure 2B, S2A) their localization in P9 WT, Snail Tg, and Snail Tg/Min KO (Mindin knockout) skin.…”
Section: Resultsmentioning
confidence: 99%
“…Our data reveals Mindin as a novel modulator of heterogeneous dermal fibroblasts that drive cutaneous fibrogenesis (Figure 5E). We have shown that Mindin is secreted by Snail Tg keratinocytes 21 and elicits unique functional responses in resident subpopulations of fibroblasts in the skin. Mindin mediates migration of Sca1+ fibroblasts via Fyn kinase and increases inflammatory cytokine production in these cells.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations